(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2018)
The aim of this report is to provide systematic analysis of studies investigating ICT tools for children with Autistic Spectrum Disorders. They are categorized into ICT assessment tools and ICT intervention tools. The review outlines the origin of each tool; their functionality by describing certain technological features they possess, and how they contribute to this field. On one hand, many ICT tools contribute in the diagnosis of ASD; on the other hand, ICT intervention tools play an important role, trying to enhance both cognitive and social abilities of the ASD child. Through the review of these articles, we try to analyze in depth how far they have come in addressing what has turned out to be a need in education in Chile.